Operation endurance - Gunn, S. M. (New York : HarperCollins, 2002)
A Russian scientist carries information about a mission to seek and co biological weapons under production on a Russian island
Keywords: United States. -- Navy. -- SEALs -- Fiction; Defectors -- Russia -- Fiction; Nuclear submarines -- Fiction; Biological weapons -- Fiction; Weapons of mass destruction -- Fiction; Bering sea coast (Russia) -- Fiction; War stories